Isolation, Characterization, and RP-HPLC Estimation of P-Coumaric Acid from Methanolic Extract of Durva Grass (Cynodon dactylon Linn.) (Pers.). (18th February 2015) - Karthikeyan, Ramadoss; Devadasu, Chapala; Srinivasa Babu, Puttagunta
Abstract : P-coumaric acid is a nonflavonoid phenolic acid and is a major constituent of the species Cynodon dactylon Linn. (Pers.). In this study isolation of P-coumaric acid was achieved by preparative TLC and the compound thus isolated was characterised by UV, mass, and H 1 NMR spectral analysis. An isocratic RP-HPLC method was developed for the estimation of P-coumaric acid from methanolic extracts of durva grass. The chromatographic separations were achieved by RP-C18 column (250 mm × 4.6 mm, 5 μ ), Shimadzu LC-20AT Prominence liquid chromatograph, and a mobile phase composed of water : methanol : glacial acetic acid (65 : 34 : 1 v/v). The flow rate was 1.0 mL/min and the analyses of column effluents were performed using UV-visible detector at 310 nm. Retention time of P-coumaric acid was found to be 6.617 min. This method has obeyed linearity over the concentration range of 2–10 μ g/mL and the regression coefficient obtained from linearity plot for P-coumaric acid was found to be 0.999. RP-HPLC method was validated in pursuance of ICH guidelines.